Growth Ring Pattern in the Otolith of Mudskipper (Periopthalmodon schlosseri, Pallas 1770) from the Mangrove and Sri Laksamana Harbor, Bengkalis District, Riau Province. - Megawati Megawati; Windarti Windarti; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractGrowth of fish is affected by environmental conditions. As growth pattern is reflected on the growth ring pattern in the otolith, growth pattern variations caused by environmental condition will also be reflected in the growth ring pattern in the otolith. Mudskipper was present in 2 different areas namely in the mangrove ecosystem and around the harbor area.  To understand the growth ring pattern of the fish from those areas, a study has been conducted on August to October 2018.  Fifty seven fishes were captured, 32 fishes (15 males and 17 females, 135-215 mm of TL, 16-185 g of BT) from the mangrove and 25 fishes (9 males and 6 females, 150-230 mm of TL, 35-141 g of BT) from the harbor. The otolith was removed, processed, and growth ring pattern was checked using a binocular microscope. Results shown that dark growth ring pattern in the fish from the harbor and mangrove was different. The mangrove fishes has 1-4 dark growth ring, while the harbor fishes have 2-9 dark growth ring . The quantity of dark ring in otolith shown that the fish from the mangrove grew better than the fishes from the harbor.Keywords :environmental conditions, otolith ring, amphibious fish, growth pattern.